2000
DOI: 10.1042/0264-6021:3520117
|View full text |Cite
|
Sign up to set email alerts
|

In vitro membrane-inserted conformation of the cytochrome b5 tail

Abstract: The cytochrome b(5) tail is a 43-residue membrane-embedded domain that is responsible for anchoring the catalytic domain of cytochrome b(5) to the endoplasmic reticulum membrane. Different models for the structure of the membrane domain of cytochrome b(5) have been proposed, including a helical hairpin and a single transmembrane helix. In the present study, CD spectroscopy was used to investigate the conformation of the tail in different environments, and as a function of temperature, with the goal of understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…208 and 223 nm (Fig. 5a), respectively, which is similar to that of the other heme-containing proteins [98,99]. The CD spectrum of Mb-[bmim]BF 4 -SWNTs (Fig.…”
Section: Spectroscopic Characterizationmentioning
confidence: 72%
“…208 and 223 nm (Fig. 5a), respectively, which is similar to that of the other heme-containing proteins [98,99]. The CD spectrum of Mb-[bmim]BF 4 -SWNTs (Fig.…”
Section: Spectroscopic Characterizationmentioning
confidence: 72%
“…4C) (34). A few studies have suggested that the tight binding form might represent a membrane-spanning conformation (19,(35)(36)(37). No examples of stable integral membrane protein structures that span only one-half of the bilayer in a hairpin conformation have been identified in the high resolution x-ray structures of the membrane proteins determined to date.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of the proteins studied, including several SNARE proteins, are initially targeted to the ER and only six proteins, including the trans outer membrane proteins TOM-5, -6, -7 and -22 are targeted directly to the MOM [7 -12]. The mechanisms of targeting of the mammalian VAMP/SNARE proteins, the two isoforms of cytochrome b5 (ER-specific and MOM-specific cyt.b5) and the Bcl-2 family members have also been investigated [5,[11][12][13][14][15][16][17][18][19][20][21]. Among these studies, saturable, ATP-and receptor-dependent, as well as non-saturable, ATP-and receptor-independent mechanisms have been described using in vitro assays.…”
Section: General Mechanisms Of Tail-anchoring Into the Membrane Of Thmentioning
confidence: 99%
“…[3]). Tail-anchored proteins are specifically targeted to and inserted into either the MOM or the ER membrane via the hydrophobic TMD, which varies in length between 15 and 22 aa and is suggested to span the membrane once in an a-helical conformation [3,5]. Once inserted into the membrane, the N-terminal bulk of the protein faces the cytosol.…”
Section: General Mechanisms Of Tail-anchoring Into the Membrane Of Thmentioning
confidence: 99%